Cesiribacter roseus sp. nov., a pink-pigmented bacterium isolated from desert sand - Ming Liu; Huan Qi; Xuesong Luo; Jun Dai; Fang Peng; Chengxiang Fang (2011)
A pink-pigmented, Gram-negative, rod-shaped, motile, strictly aerobic bacterium, designated strain 311(T), was isolated from desert sand in Xinjiang, China. Phylogenetic analyses based on 16S rRNA gene sequences showed that strain 311(T) was related closely to Cesiribacter andamanensis AMV16(T) (94.6% similarity). The DNA G+C content of strain 311(T) was 47.1 mol% and the major respiratory quinone was menaquinone 7 (MK-7). The main cellular fatty acids were C(16:1)ω5c (29.9%), iso-C(15:0) (21.9%), iso-C(17:0) 3-OH (13.3%) and summed feature 4 (iso-C(17:1) I and/or anteiso-C(17:1) B; 13.0%). Based on phenotypic and chemotaxonomic data and phylogenetic analysis, strain 311(T) is considered to represent a novel species of the genus Cesiribacter, for which the name Cesiribacter roseus sp. nov. is proposed. The type strain is 311(T) (=CCTCC AB 207142(T) =KACC 15456(T)).